A Comparative Analysis of East and West African Cotton Cloth Production from the Early Modern to the Post-colonial Era - Katharine Frederick (African Economic History Network (AEHN), 2018)
This article examines why "traditional" cotton textiles industries tended to decline in southern and central East Africa during the late-nineteenth and early-twentieth centuries while cloth production persisted in much of northern East Africa and West Africa - where per-capita cloth imports were significantly higher - well into the post-colonial period. Comparative analysis reveals that relatively resilient industries tended to arise and persist where textile traditions were adopted comparatively early, allowing industries and demand for domestic cloth to develop several centuries before global integration and colonization; in areas with relatively dense populations and access to large markets; where centralized states developed and pre-colonial institutions helped encourage industrial growth; where local endowments and geography favored income-enhancing cash-crop cultivation; and where nineteenth- and twentieth-century colonial intervention and fiscal institutions were comparatively less disruptive to existing socio-economic organization.
Keywords: N17; N37; N67; 330; cotton textiles; deindustrialization; East Africa; West Africa